PENGAWETAN ROTAN KURANG DIKENAL SEBAGAI BAHAN BAKU MEBEL MENGGUNAKAN RENDAMAN DINGIN - Hamdi, Saibatul (Kementerian Perindustrian, 2012)
This research used the lesser known species as much 5 types rattan, consisted of i.e marau (Calamus Mettanensis Becc), toho (Calamus Spp), galang (Daemonorops Verticilaris Griff Mart), hijau (Calamus Spp) and simpurut (Calamus Panajuga Becc) from Central Kalimantan. Preservative used the mixture of boric acid with the borax and copper-8 byÂ the concentration of 1,0 %, 2,0 % and 3,0 %. Soaked time during 2 day, 4 day and 6 day by immersion chilled. Result of research indicated that the retention value varied, the greater of concentration condensation and soaking period, the greater average the value of retention while penetration result at all of treatment showed the value 100 %.Keywords: Â rattan, preservation, retention, penetration, cold soaking.